Multinational Corporations and International Environmental Law : What Should the Future Look Like? Experiences from the Private Sector Participation within the UNFCCC Regime - Vähä-Piikkiö, Agda (fi=Turun yliopisto|en=University of Turku|, 2018)
Due to the globalisation and liberalisation of international trade, multinational corporations have gained economic powers exceeding those of many states. While their day-to-day business activities may create significant stress to the environment, the control of their conduct in respect of the environment is often ineffective or missing. To find feasible solutions to this imbalance, this thesis is interested in the possible ways of integrating multinational corporations into the sphere of international environmental law, taking into account their participation in policy-making and in the implementation of international instruments, in order to enhance their environmental performance. This thesis aims to offer one step forward towards eventually more effective international environmental law. It will provide useful insight for everyone participating in environmental policy-making, including government officials, international organisations, and the multinational corporations themselves. The research combines the legal dogmatics and sociology of law methods. In addition, it includes a case study on corporate involvement within the UNFCCC regime, focusing especially on the decision- making within the regime and the efficacy of the market mechanisms in incentivising corporations and producing environmentally positive effects. The issue of the environmental responsibilities of multinational corporations has not been effectively addressed at the international level. Nevertheless, the importance of integrating the private sector into action has been widely acknowledged in international soft law instruments, but the regulation is based on voluntary action. The shortcomings of international law have left a cap to fill in for self-regulatory initiatives. Indeed, multinational corporations have become de facto actors, and the traditional concept of personality might still hinder positive regulatory developments. Within the UNFCCC regime, especially the Clean Development Mechanism and the Joint Implementation have managed to incentivise corporate participation, but the environmental effects of these mechanisms have been more ambiguous. In order to enhance its own effectiveness, international environmental law should develop towards more inclusive environmental governance, requiring the redefinition of international legal personality. Furthermore, market mechanisms may offer one solution for incentivising multinational corporations to enhance their environmental responsibility, but as environmental policy tools, they seem to require a strong framework and adequate monitoring in order to provide concrete environmental benefits.